2023
DOI: 10.4322/bds.2023.e3775
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different framework s material on strain induced in distal abutment in mandibular Kennedy s class II: an in-vitro study

Noha Mohamed EL HUSSIENY FAYAD,
Dina Essam BAHIG

Abstract: How to cite: El Hussieny Fayad NM, Bahig DE. The effect of different framework's material on strain induced in distal abutment in mandibular Kennedy's class II: an in-vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Results by Villefort et al [39] showed that PEKK has lower stress concentration values as a prosthetic screw & base in full arch prosthesis under the" all-on-four" concept while lower stress concentration was observed on PEEK frameworks. A study by El Hussieny et al [40] was in contrast to findings by Alsadon et al [11] as the first reported that the PEEK group showed lesser strain values in comparison to PEKK. while Alsadon showed that PEKK had better mechanical The limitations of the study included only one-way surface pretreatment using air abrasion with Al 2 O 3 particles.…”
Section: Discussionmentioning
confidence: 67%
“…Results by Villefort et al [39] showed that PEKK has lower stress concentration values as a prosthetic screw & base in full arch prosthesis under the" all-on-four" concept while lower stress concentration was observed on PEEK frameworks. A study by El Hussieny et al [40] was in contrast to findings by Alsadon et al [11] as the first reported that the PEEK group showed lesser strain values in comparison to PEKK. while Alsadon showed that PEKK had better mechanical The limitations of the study included only one-way surface pretreatment using air abrasion with Al 2 O 3 particles.…”
Section: Discussionmentioning
confidence: 67%